Evaluation of some production parameters in piglets at weaning with different diets (Revista Sistemas de Producción Agroecológicos, 2014)
This work was carried out on the farm San Nicolas belonging town Cumaral, Meta, Colombia. 18 sows with their litters were used, which were divided into three treatments: the first group of piglets fed milk only (G1), the second with the same adding commercial concentrate (G2) and third, like adding a formulated diet (G3). The statistical design was a randomized complete block three treatments, two blocks of six repetitions. Piglets were weighed at birth, continuing weighing daily from the fifth day of age until weaning at 21 days. No significant differences (P>0.01) were found in terms of weight gain, feed intake, feed conversion or for weaning weight (P>0.05). The results suggest that although breastfeeding no significant differences (P>0.05) between production parameters studied, the power is found during the early stages of life of the piglets can determine the subsequent performance of the same. Preinitiation food consumption during the breastfeeding helped keep the weight of piglets when they had diarrhea.
Keywords: suckling pig; breastfeeding; weaning